Utilization of cellulose nanocrystals (CNC) as a filler for chitosan-based films for chili peppers packaging - Alanas, Edith; Erdawati, Erdawati; Saefurahman, Ganjar; Amiril Sahab, Abdul Sani (IOP Publishing Ltd, 2021)
This study investigates the effects of the percentage of cellulose nanocrystals (CNC) on chitosan film for wrapping chili peppers during storage at room temperature for 12 days. The chitosan-CNC film's characterization was analyzed by SEM, FTIR, and physical properties were measured based on tensile strength, percent elongation, water solubility, and degradation rate. This research used a randomized design with four treatments and two replications. The treatments in this study were E0 = control, E1 = CNC 1 %, E3 = CNC 3 %, E5 = CNC 5 % and E10 = CNC 10 %. The quality of chili peppers was analyzed based on the concentration of vitamin C, titratable acidity, total soluble solids, and weight loss rate. The E3 treatment achieved the best results on day 12, i.e., weight loss of chili peppers with the chitosan-CNC film was 0.51 %, vitamin C was 295 mg/100 g, titratable acidity was 0.25 %, and the total soluble solid was 24%.